2005
DOI: 10.1002/humu.9371
|View full text |Cite
|
Sign up to set email alerts
|

Thromboxane synthase (TBXAS1) polymorphisms in African-American and Caucasian populations: evidence for selective pressure

Abstract: Thromboxane synthase (TBXAS1), a cytochrome P450 enzyme, converts prostaglandin H2 into thromboxane A2, a potent vasoconstrictor and inducer of platelet aggregation. Thromboxane A2 has been implicated in modulating cell cytotoxicity and in tumor growth and metastasis. Twelve coding-region variants were identified in the human TBXAS1 gene in 48 African-American and 46 Caucasian individuals, of which eight were amino-acid substitutions. The latter were confirmed in an independent Caucasian population (n=94 unrel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…There are many genetic variations between the ethnic groups that affect the platelet function. While the ethnic differences in glycoprotein IIIa gene polymorphism remain to be established, [34] the cyclooxygenase polymorphisms are confirmed in the African-American population [35,36]. thromboxane synthase (TXS) polymorphism (TBXAS1) may have particular importance to this study, since TXS, a cytochrome P450 enzyme, converts prostaglandin H2 into thromboxane A2, a potent inducer of platelet aggregation [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…There are many genetic variations between the ethnic groups that affect the platelet function. While the ethnic differences in glycoprotein IIIa gene polymorphism remain to be established, [34] the cyclooxygenase polymorphisms are confirmed in the African-American population [35,36]. thromboxane synthase (TXS) polymorphism (TBXAS1) may have particular importance to this study, since TXS, a cytochrome P450 enzyme, converts prostaglandin H2 into thromboxane A2, a potent inducer of platelet aggregation [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…(3). High K a :K s ratios (>2:1) are consistent with a strong positive selection for evolutionary change (reviewed in [Kreitman 1999]), as proposed for the thromboxane synthase (TBXAS1, K a :K s 6:1) and adipokine (ANGPTL4, K a :K s 4:1) genes [Cargill 1999;Romeo 2007;Ulrich 2005]. The high K a :K s ratio found in SLC13A1, together with the high allelic frequency (range = 22.5 to 40.4%) of N174S (Table 3) which leads to 60% loss of SO 4 2-transport function [Lee 2006], implies that reduced NaS1 function may have provided a biological benefit to human evolution and may be relevant when considering human exposure to environmental and dietary chemicals activated by sulfonation, which are implicated with certain cancers and adverse drug reactions [Gamage 2006;Glatt 2000].…”
Section: Distribution Of Snps Among Sulfate Transporter Genesmentioning
confidence: 84%
“…Further, human TXAS mutations have been linked to a bone density disorder [14]. Fourteen non-synonymous polymorphisms in the TXAS coding region were identified in the first three reports on variations in the gene [15,16,17], with evidence for selective evolutionary pressure against genetic mutations in the gene [17]. In view of the roles of TXAS in physiology and pathology, it is important to understand the effects of human TXAS protein variants on catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…We have developed a prokaryotic expression system that provides sufficient recombinant TXAS with ~90 % purity for enzymatic characterization [18,19]. Structural analysis based on homology modeling suggested that four of the TXAS variants (K258E, Q417E, E450K and T451N) were likely to have altered enzymatic activities [17]. In addition, the L357V variant, which has a minor allele frequency of almost 11% in African-Americans [17] was predicted to have altered catalytic activity by the PolyPhen algorithm [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation